A REVIEW ON EFFECTS OF CARDIOTOXIC DRUGS IN ANIMAL MODELS - Alsuwayt, Bader (Journal of Liaquat University of Medical & Health Sciences, 2021)
The major types of Cardiotoxicity in humans are mainly drug-induced, trauma, and stress-induced. Animal models for drug-induced Cardiotoxicity are generated by using various categories of drugs including anticancer, antiretroviral and antidiabetic, etc. Many of these drugs induce Cardiotoxicity via altering ‘redox homeostasis’ by rising the generation of oxygen radicals. Apart from this, many other drugs utilize a different pathway to promote cardiac damage. Here we describe the various categories of drugs that produce Cardiotoxicity by different mechanisms in various animals and cell line methods. Each category of the drug utilizes different pathways to induce Cardiotoxicity, leads to change in the enzyme level and in vivo parameters which can be used as biomarkers. This review gives an idea to the investigator for the section of appropriate animal models to achieve the objectives of the experiment. Identification of lead molecules and selection of a correct drug to induce Cardiotoxicity by using experimental data may allow the investigator to come out with desired outcomes. Key words: Animal models, drug-induced Cardiotoxicity, biomarkers